24.7k views
4 votes
How can the square-root property be used to solve y2=6

1 Answer

2 votes

Given the expression:


y^2=6

The first step to solve it using the square root property, is moving the coefficient on the right side of the equation to the left side, changing it's sign:


\begin{gathered} y^2=6 \\ \Rightarrow y^2-6=0 \end{gathered}

Now, remember the rule for conjugates:


(a+b)(a-b)=a^2-b^2

in this case we have the following:


\begin{gathered} y^2=a^2 \\ \Rightarrow y=a \\ b^2=6 \\ \Rightarrow b=\sqrt[]{6} \end{gathered}

therefore, we can factor the expression like this:


\begin{gathered} y^2-6=0 \\ \Rightarrow(y-\sqrt[]{6})(y+\sqrt[]{6})=0 \end{gathered}

Finally, we have that the only values that make true the expression are:


\begin{gathered} y_1=\sqrt[]{6} \\ y_2=-\sqrt[]{6} \end{gathered}

User BryanP
by
5.2k points